2019
DOI: 10.7150/ijms.37427
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles-loaded anti-miR221 enhances antitumor effect of sorafenib in hepatocellular carcinoma cells

Abstract: Objective: Currently, sorafenib is the main systemic chemotherapy drug for advanced stage of hepatocellular carcinoma (HCC). However, emerging data from some clinical HCC patients indicates that sorafenib alone has only moderate antitumor efficacy, and could not inhibit metastasis and progression of disease. MiR-221 plays a role in promoting tumorigenesis in HCC by inhibiting the expression of p27. In this study, we analyzed the synergistic anti-tumor effects of sorafenib and gold nanoparticles-loaded anti-miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…miRNA is involved in cell regulation, including cell metabolism, cell proliferation, cell apoptosis, differentiation, and cell response, after virus infection [ 40 ]. Cai et al [ 41 ] demonstrated that sorafenib and AuNP–anti-miRNA-221 combination treatment exerts an anticancer effect on HCC via inhibiting miRNA-221/p27/DNMT1 signalling pathway. Lu et al [ 42 ] uncovered the interaction between FLJ33360 and miRNA-140.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is involved in cell regulation, including cell metabolism, cell proliferation, cell apoptosis, differentiation, and cell response, after virus infection [ 40 ]. Cai et al [ 41 ] demonstrated that sorafenib and AuNP–anti-miRNA-221 combination treatment exerts an anticancer effect on HCC via inhibiting miRNA-221/p27/DNMT1 signalling pathway. Lu et al [ 42 ] uncovered the interaction between FLJ33360 and miRNA-140.…”
Section: Discussionmentioning
confidence: 99%
“…New data obtained from some patients with HCC in clinical trials suggest that miR221 plays a role in promoting tumorigenesis in HCC by inhibiting the expression of p27 154 . Cai et al investigated the synergistic inhibition of HCC cell proliferation by the combination of SOR and anti-miR221 conjugated to gold NPs 155 . The miRNA therapy increased the inhibitory effect of SOR on cell proliferation by inhibiting the miR221/p27/DNMTI signaling pathway.…”
Section: Combining Sor With Other Treatments For Synergistic Theramentioning
confidence: 99%
“…Likewise, gold nanoparticles loaded with anti-miR-221 were used to deliver the anti-miR to HCC cells in vitro. Using these nanoparticles, it was also found that anti-miR-221 could enhance the sensitivity of HCC cells to sorafenib [ 110 ]. Another notable strategy to address the issue with miRNA delivery has been the modification of miRNA itself [ 26 , 30 , 119 ].…”
Section: The Role Of Mirnas In Developing Therapeutics Targeting Gmentioning
confidence: 99%